Genome size determination in chagas disease transmitting bugs (hemiptera-triatominae) by flow cytometry (2007)
ABSTRACT: Because information about genome size in triatomines is scarce and contradictory, we performed DNA quantification by flow cytometry in 13 species belonging to five genera (Dipetalogaster, Eratyrus, Panstrongylus, Rhodnius, and Triatoma) to infer overall tendencies and phylogenetic associations. The results show that the haploid DNA content of the subfamily Triatominae varies nearly 4-fold, from < 0.7 pg in Rhodnius species (0.6 × 109 bp) to 2.7 pg in Triatoma delpontei (2.6 × 109 bp). Considering that triatomines present similar chromosome numbers, we suggest that genome size differences are the result of variation in the quantity of repetitive DNA sequences localized in hetero and euchromatin. Changes in heterochromatin are particularly important when considering populations or closely related species; in more distant taxa, euchromatic changes also play a role. Our analyses indicate that flow cytometry is a useful tool for population, taxonomic, and evolutionary studies in this subfamily.